2011
DOI: 10.1038/onc.2011.449
|View full text |Cite
|
Sign up to set email alerts
|

Small nucleolar RNA 42 acts as an oncogene in lung tumorigenesis

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer death, reflecting the need for better understanding the oncogenesis, and developing new diagnostic and therapeutic targets for the malignancy. Emerging evidence suggests that small nucleolar RNAs (snoRNAs) have malfunctioning roles in tumorigenesis. Our recent study demonstrated that small nucleolar RNA 42 (SNORA42) was overexpressed in lung tumors. Here, we investigate the role of SNORA42 in tumorigenesis of NSCLC. We simultaneously assess geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
220
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(246 citation statements)
references
References 36 publications
17
220
0
2
Order By: Relevance
“…21 For example, SNORA42 has been shown to act as a potential oncogene in the development and progression of lung cancer. 22 Furthermore, homozygous and heterozygous deletions in U50, a C/D snoRNA, have been described in prostate and breast cancer tissues, respectively. 23,24 On the other hand, there are some preliminary data showing that the genes that host snoRNAs might also contribute to cancer pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…21 For example, SNORA42 has been shown to act as a potential oncogene in the development and progression of lung cancer. 22 Furthermore, homozygous and heterozygous deletions in U50, a C/D snoRNA, have been described in prostate and breast cancer tissues, respectively. 23,24 On the other hand, there are some preliminary data showing that the genes that host snoRNAs might also contribute to cancer pathogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…snoRNA are non-coding RNAs (ncRNA) that are less well known than other ncRNAs, such as miRNAs and siRNAs, that could be actively involved in the development of cancer. [44][45][46][47] In this setting, global downregulation is a characteristic feature of snoRNAs in cancer cells. For example, it has been recently reported that leukemic cells show infraexpression of several snoRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Recent new cellular functions have led us to hypothesize that snoRNA accumulation patterns could be modulated in cancer. [10][11][12]14,[30][31][32][33][34][35] Acute leukemia is a good model to try to answer this question as it is characterized by restrictive oncogenic events leading to a blockade in differentiation.…”
Section: Discussionmentioning
confidence: 99%